Efeito dos métodos de envelhecimento artificial sobre a resistência de união de sistemas adesivos aplicados à dentina - Sutil, Bruna Gabrielle da Silva (2021)
In the present work, two studies on the most commonly used methods of artificial aging will be presented, as well as relating the degradation method that has the greatest influence on the different classes of adhesives. The first paper, an in vitro study, evaluated which artificial aging method more negatively affects the microshear bond strength (μSBS) of four categories of adhesive systems. 150 caries-free human third molars (n=5) were prepared and randomly divided according to the aging method (water storage for 24 hours or 6 months - WS, sodium hypochlorite storage for 1 or 5 hours – NaOCl, thermocycling with 10,000 or 30,000 thermal cycles – TC), and adhesive/approach (a three-step, etch-and-rinse - Scotchbond Multi-Purpose (SBMP); a two-step, etch-and-rinse - Single Bond 2 (SB2); a two-step, self-etch - Clearfil SE Bond (CSE) and an universal adhesive- Scotchbond Universal applied in self-etch (SBU/SE) and etch-and-rinse (SBU/ER) mode. μSBS results were subjected to two-way ANOVA and post hoc Bonferroni tests (p<0.05), in addition to the Kaplan-Meier analysis to produce the survival curves. The results showed that the aging method and adhesive factors, as well as the interaction of the factors were statistically significant (p = 0.00). The more deleterious aging method was 30,000 thermo cycles which affected the SBMP, CSE and SBU/SE adhesives. Kaplan-Meier survival curves revealed that aging methods influenced each adhesive system differently. It is concluded that the aging methods promote distinct effects for each of the adhesive classes, except for storage in water for 6 months, which did not affect the bond strength of the adhesives negatively. In the second study, a methodologic review was carried out, covering the literature from 2011 to 2021, to establish the most frequent artificial aging method when performing adhesive strength tests, and also to verify if there is any correlation between the chosen protocol and the adhesive system tested. For this study, the following inclusion criteria were applied: original study, published in English, in vitro studies showing some method of artificial aging, with experiments performed on dentin and that presented some microbond test. From a total of 5,248 articles found in the search, 387 studies were selected after preliminary evaluation and removal of duplicates. Two independent reviewers applied the inclusion criteria, resulting in 27 articles screened to be read in full. Methodology and results data were reviewed and extracted to identify the most frequently used aging method and adhesive systems. It was observed that aging in water, with varied storage periods, and thermocycling with different number of cycles were the most frequent aging methods in the selected literature. Among the tested adhesives, the most used was the universal adhesive system. However, no correlation was found between the aging protocol and adhesive system tested.